Neoliberalism at a Crossroads - Pupolizio, Ivan (Soft Power, 2024)
Not so many years ago, Flew argued that, in a relatively short period of time, the term “neoliberalism” had become “a kind of conceptual trash-can, into which anything and everything can be dumped, as long as it is done so with suitable moral vehemence” (Flew, 2014, p. 67). Although scholars cautioned early on against “reify[ing] neoliberalism and treat[ing] it as a phenomenon which manifests itself everywhere and in everything” (Gamble, 2001, p. 134), Flew asserts that “this is in fact what has happened to neoliberalism over the last decade” (Flew, 2014, p. 51). She offers an astounding number of —sometimes amusing— examples that illustrate how the term has been used in this very way, in contexts ranging from the space dedicated to books in Australian public libraries to the popularity of Bollywood-style weddings (p. 51).